Analysis of the content of the Kurdish curriculum for grades one to six based on caring for people with disabilities - Abdulrahman, Asst.L.Gharib Aziz (Sulaimani Journal for Humanities, 2025)
People with disabilities are those who have complete or partial physical or emotional disabilities, or have learning disabilities throughout their lives or for a certain period of their lives People with disabilities The research community includes all Kurdish textbooks for grades (16) books, and the sample of the research includes Kurdish textbooks for grades (1 to 6) which number (10) books, as well as tools Data collection is a checklist of subjects and pictures in books. The results of the study show that the Kurdish textbook curriculum for grades (1 to 6) does not pay much attention to people with disabilities, the small number that exists is random and scientific Therefore, the content of these books cannot educate students to respect people with disabilities.